The Fourth Political Theory - al-Hussein, Huda Abd al-Ghaib Abd; Shabib, Asaad Kazem (Journal of Ecohumanism, 2025)
The fourth political theory proposed by the Russian philosopher (Alexander Dugin) included a set of political ideas, principles and practices that developed in the twentieth century. Dugin considered his theory to be a reaction to traditional political theories, such as the liberal theory, the communist theory, and the fascist theory.,The fourth political theory expressed a desire to go beyond the traditional divisions of political ideas, and presented a new vision, which included a number of principles and ideas from previous theories. It took cooperation and competition from liberalism, took the desire to establish the Russian Empire, and restore the glories of the Soviet Union from communist theory, and took the interest and focus on cultural and national identities from fascist theory. Therefore, Dugin emphasized that his theory does not represent an extension of previous theories, but rather is a comprehensive theory for all ages and for different human groups.